An investigation on shelf life and sorbate residues of salt and potassium sorbate - Ayşe Gürel İnanlı; Bahri Patır (Eurasian Journal of Veterinary Sciences)
In this study, chemical, microbiological and sensorial changes during processing and storage of potassium sorbate treated salt-cured trout fillets were investigated. For this purpose; %10 and %15 ratios NaCI and %1, %5 and %10 ratios potassium sorbate were treated to the fillets. The processed fillet samples were vacuum-packaged in polyethylene bags and storaged at 4 CB. The samples were analyzed physicochemically (pH, moisture, salt, TVB-N, number of TBA and sorbic acid amounts) and microbiologically (mesophile aerob bacteri, yeast and mould countings) in some periods of production (fillet, end of salting and drying) and in the storage days ol 7, 14, 28, 42, 56, 70 and 84. In addition, 8 panellists evaluated the samples for sensory attributes on days 7,14, 29, 42. 56 and 70 during storage. In study, the antimicrobial effect of potassium sorbate was increased by increasing salt level during processing; thus, a synergistic effect was observed between salt and potassium so ibate. The chemical quality was found to be better depending on processing types. When potassium sorbate treated in different concentrations, the sorbic acid amounts in the product were found in different levels. However, this amounts had no health risk for normal human consumption. Sensorial analyzes showed that the consumable properties of potassium sorbate treated samples was better than no potassium sorbate treated samples minimum 70 days. It could be come into conclusion that trout lillet treated with described technological process in this study could be kept without spoilage under suitable storage condilions for at least 70 days.